Evaluating the accuracy of two different age estimation methods in growing children in Navi Mumbai using Orthopantomograph: A radiographic study - Shilpa Naik; Nithi Rajadhyaksha; Kiran Dattatray Ghule (Wolters Kluwer Medknow Publications, 2021)
Background: Age estimation through dental maturity indicators is relatively more accurate, reliable, and valid for living as well as dead individuals. It acts as an important tool in diagnosis and treatment planning in clinical as well as in forensic dentistry. There are various methods to estimate the dental age. Out of which, Demirjian's method has been widely used in various populations. However, there is a dearth of literature on Indian population comparing Demirjian's method to Cameriere's method. Aim: The purpose of this study was to evaluate the accuracy of Demirjian's and Cameriere's age estimation methods to chronological age in growing children using orthopantomograph (OPG). Setting and Design: The sample consisted of digital OPGs of 280 children in Navi Mumbai aged 5-16 years. Materials and Methods: Digital OPGs were used to assess the dental maturity of seven mandibular left teeth using Demirjian and Cameriere's method and were compared to the chronological age. Statistical Analysis Used: Data were analyzed using Student's t tests. Result: Irrespective of gender, dental age estimated by Cameriere's method (mean 10.23 ± 2.79 years), underestimated the chronological age (mean 11.74 ± 2.86 years) for overall population which showed statistically significant difference. Demirjian's method overestimated (mean 12.24 ± 3.06 years) the chronological age for the overall population but was statistically insignificant. Conclusion: Demirjian's method is more closely in correlation with the chronological age of growing children as compared to the Cameriere method when applied to children of age 5-16 years in Navi Mumbai.